Multiple statistical models reveal specific volatile organic compounds affect sex hormones in American adult male: NHANES 2013–2016 - Wei, Chengcheng; Cao, Li; Zhou, Yuancheng; Zhang, Wenting; Zhang, Pu; Wang, Miao; Xiong, Ming; Deng, Changqi; Xiong, Qi; Liu, Weihui; He, Qingliu; Guo, Yihong; et al. (Frontiers in Endocrinology, 2023)
Background: Some VOCs are identified as endocrine-disrupting chemicals (EDCs), interfering with the effect of sex hormones. However, no studies focused on the common spectrum of environmental VOCs exposure affecting sex hormones in the average male population. Objectives: We aimed to explore the association between VOCs and sex hormones in American adult males using multiple statistical models. Methods: The generalized linear (GLM), eXtreme Gradient Boosting (XGBoost), weighted quantile sum (WQS), Bayesian kernel machine regression (BKMR) and stratified models were used to evaluate the associations between Specific Volatile Organic Compounds and sex hormones in American adult male from NHANES 2013–2016. Results: Pearson correlation model revealed the potential co-exposure pattern among VOCs. XGBoost algorithm models and the WQS model suggested the relative importance of VOCs. BKMR models reveal that co-exposure to the VOCs was associated with increased Testosterone (TT), Estradiol (E2), SHBG and decreased TT/E2. GLM models revealed specific VOC exposure as an independent risk factor causing male sex hormones disorders. Stratified analysis identified the high-risk group on the VOCs exposures. We found Blood 2,5-Dimethylfuran in VOCs was the most significant effect on sex hormones in male. Testosterone increased by 213.594 (ng/dL) (124.552, 302.636) and estradiol increased by 7.229 (pg/mL) for each additional unit of blood 2,5-Dimethylfuran (ng/mL). Conclusion: This study is an academic illustration of the association between VOCs exposure and sex hormones, suggesting that exposure to VOCs might be associated with sex hormone metabolic disorder in American adult males.